Human Papillomavirus Type 16 Sequence Variation in Concurrent Vulvar and Penile Carcinoma in a Married Couple. Issue 6 (June 2015) - Mitamura, Takashi; Watari, Hidemichi; Yamashiro, Katsushige; Kato, Tatsuya; Hosaka, Masayoshi; Shimada, Chisa; Fukumoto, Shun; Noshiro, Kiwamu; Sasaki, Takayuki; Sakuragi, Noriaki
<x xml:space="preserve">Abstract</x> Abstract We encountered an elderly married couple with concurrent vulvar and penile carcinoma with an Asian variant of human papillomavirus type 16. Asian variants might have an elevated risk of concurrent external genital carcinomas of a male and a female, and analysis of human papillomavirus variants might be important to understand the mechanism of carcinogenesis.